2016
DOI: 10.1200/jco.2015.62.2860
|View full text |Cite
|
Sign up to set email alerts
|

Global Health Equity: Cancer Care Outcome Disparities in High-, Middle-, and Low-Income Countries

Abstract: Breakthroughs in our global fight against cancer have been achieved. However, this progress has been unequal. In low- and middle-income countries and for specific populations in high-income settings, many of these advancements are but an aspiration and hope for the future. This review will focus on health disparities in cancer within and across countries, drawing from examples in Kenya, Brazil, and the United States. Placed in context with these examples, the authors also draw basic recommendations from severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
164
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(171 citation statements)
references
References 24 publications
2
164
0
5
Order By: Relevance
“…These cancers are concentrated among the poor in middle- and high-income countries, and prevention and early detection should be a high, targeted priority. 29 …”
Section: Discussionmentioning
confidence: 99%
“…These cancers are concentrated among the poor in middle- and high-income countries, and prevention and early detection should be a high, targeted priority. 29 …”
Section: Discussionmentioning
confidence: 99%
“…56 It is suggested that given the high population burden of preventable cancers, these cancers should be prioritised in lowincome countries, while in middle-income settings, risk reduction and adhering to the WHO essential list of medications is warranted. 57 Reductions in the comprehensiveness of care may shift the financial burden to employers or households and will usually increase the role of out-of-pocket costs or co-payments in the health system. This has the potential for patients to delay seeking treatment and promote inefficiencies by encouraging people to use resource-intensive emergency services instead of cost-effective primary care.…”
Section: Potential Impact Of Reaching the Sustainability Ceiling Of Cmentioning
confidence: 99%
“…Given the chronicity of cancer and very high treatment costs, even moderate co-payments would mean that access to treatment could become dependent on a patient's ability to pay. 63 Evidence shows that young uninsured adults in the US are more likely to present with advanced disease, be undertreated, or die after a diagnosis of cancer compared with those who are insured, 57 with co-payments potentially further increasing these disparities.…”
Section: Potential Impact Of Reaching the Sustainability Ceiling Of Cmentioning
confidence: 99%
“…Even after "Obamacare" there are still 33 million Americans without health insurance (10.4%), 4.5 million of them children 33,34 . The risk of death for several cancers is significantly higher for insolvent patients 35,36 , bankruptcy and high debt in cancer survivors are twice that of the overall population 37 , and there is growing concern about new-drug affordability 38 .…”
Section: The Equity Mattermentioning
confidence: 99%